2017
DOI: 10.3171/2016.5.jns1645
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for recurrent vestibular schwannoma after previous resection

Abstract: V estibular schwannomas (VSs), also known as acoustic neuromas, are benign primary intracranial tumors that arise from the Schwann cells of the vestibulocochlear nerve. The incidence of VS is estimated to be 1 per 100,000 individuals per year, and it accounts for approximately 8% of all intracranial tumors in adults. 3,14 These tumors are typically slow growing (0-3.9 mm per year), but without management, most VS tumors will grow within 3 years. 4,6,14,15,18,20 For many years, microsurgical resection remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 28 publications
1
12
1
2
Order By: Relevance
“…Thus, for large or giant acoustic neuromas with significant brainstem compression or hydrocephalus, the following combined approach should be considered: initial microsurgical brainstem decompression with functional and anatomical preservation of the neural structures, followed by radiosurgery for residual tumor. 18,22…”
Section: Evolution Of Radiosurgical Treatment Planning and Postradiosmentioning
confidence: 99%
“…Thus, for large or giant acoustic neuromas with significant brainstem compression or hydrocephalus, the following combined approach should be considered: initial microsurgical brainstem decompression with functional and anatomical preservation of the neural structures, followed by radiosurgery for residual tumor. 18,22…”
Section: Evolution Of Radiosurgical Treatment Planning and Postradiosmentioning
confidence: 99%
“…Subtotal resection followed by observation or SRS, particularly for large VS, can achieve long term tumor control with improved CN preservation 67,32 . In general, small to medium VS <3 cm are managed differently than large VS, as surgery is often favored over SRS for large VS.…”
Section: Surgical Management Of Vsmentioning
confidence: 99%
“…That finding was consistent with our present findings with revision surgery; we found no recurrences after a mean follow-up of 41.5 months. In comparison, Huang et al recently reported a 94% tumor control rate with SRS for rVS after a median clinical follow-up of 74 months (47).…”
Section: Oncological Resultsmentioning
confidence: 93%